2018
DOI: 10.1093/brain/awy142
|View full text |Cite
|
Sign up to set email alerts
|

Insulin signalling promotes dendrite and synapse regeneration and restores circuit function after axonal injury

Abstract: See Peterson and Benowitz (doi:) for a scientific commentary on this article.Dendrites retract and disconnect from their cellular partners in a number of psychiatric and neurodegenerative diseases. Agostinone et al. show that injured mammalian retinal ganglion cells have the capacity to regenerate dendrites and reestablish functional connections, and identify insulin signalling as paramount for a successful pro-regenerative response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
86
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 101 publications
(126 reference statements)
10
86
0
3
Order By: Relevance
“…Although glaucoma is often overlooked as a neurodegenerative disease, it bears many similarities to other CNS diseases such as Parkinson’s, ALS, and Alzheimer’s which ultimately result in the degeneration of neurons in either the brain or spinal cord (Gupta and Yucel, 2007; Kovacs, 2017). Similar to previous studies of RGC damage as well as cortical neurons in Alzheimer’s disease (Agostinone et al, 2018; Agostinone and Di Polo, 2015; Dowjat et al, 1999; Kalesnykas et al, 2012; Williams et al, 2013), OPTN(E50K)-RGCs demonstrated significant neurite retraction and deficits in morphology compared to isogenic controls. The mechanisms to which RGC degeneration occurs in glaucoma remain somewhat inconclusive, with the most likely scenario including the interplay of numerous neurodegenerative mechanisms.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although glaucoma is often overlooked as a neurodegenerative disease, it bears many similarities to other CNS diseases such as Parkinson’s, ALS, and Alzheimer’s which ultimately result in the degeneration of neurons in either the brain or spinal cord (Gupta and Yucel, 2007; Kovacs, 2017). Similar to previous studies of RGC damage as well as cortical neurons in Alzheimer’s disease (Agostinone et al, 2018; Agostinone and Di Polo, 2015; Dowjat et al, 1999; Kalesnykas et al, 2012; Williams et al, 2013), OPTN(E50K)-RGCs demonstrated significant neurite retraction and deficits in morphology compared to isogenic controls. The mechanisms to which RGC degeneration occurs in glaucoma remain somewhat inconclusive, with the most likely scenario including the interplay of numerous neurodegenerative mechanisms.…”
Section: Discussionsupporting
confidence: 87%
“…As such, the early differentiation of OPTN(E50K) and isogenic control hPSCs yielded similar formation of optic vesicle-like and optic cup retinal organoids and a comparable number of RGCs (Supplemental Figure 1). Previous studies in animal models of RGC damage have demonstrated significant neurite retraction and dendritic remodeling in response to RGC injury and disease (Agostinone et al, 2018; Agostinone and Di Polo, 2015; Kalesnykas et al, 2012; Williams et al, 2013). To examine if this phenomenon could be recapitulated in an hPSC model, OPTN(E50K) and isogenic control RGCs were examined in a temporal fashion for their morphological characteristics associated with neuronal maturation (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation contrasts with models of glaucoma, where dendritic shrinking and functional decline prior to death is striking (Della Santina et al, 2013;Liu et al, 2011). They also seemingly contrast with other studies that observe significant dendritic shrinkage after ONC (e.g., (Agostinone et al, 2018)); however, those studies focused on broader subclasses of RGCs, so changes in dendritic area could reflect differential survival of RGC types within the subclass being assayed. It is also possible that our reliance on molecular marker expression excluded highly atrophied cells from our analysis.…”
Section: Cellular Changes In Neurons With Differential Resiliencementioning
confidence: 65%
“…Our study puts forward AAV-mediated delivery of p110δ as a novel means of stimulating regeneration through the PI3K pathway in a potentially translatable fashion. We propose that p110δ should also be considered as an additional intervention with other regenerative strategies that target the PI3K pathway, either through genetic treatment such as osteopotin and IGF-1, (Duan et al, 2015;Liu et al, 2017), expression of activated integrins or pharmacological interventions such as insulin (Agostinone et al, 2018). and obtained funding.…”
Section: Discussionmentioning
confidence: 99%